Positive correlation between uric acid and C-reactive protein serum level in healthy individuals and patients with acute coronary syndrome - Emina Spahić; Sabaheta Hasić; Emina Kiseljaković; Halima Resić; Mehmed Kulić (Medicinski glasnik, 2015)
Aim: To assess serum levels and correlation between uric acid (UA) and C-reactive protein (CRP) in acute coronary syndrome (ACS) and apparently healthy individuals. Methods: The cross-sectional study included 116 examinees of age 44 to 83 years, distributed in two groups: 80 ACS patients including 40 with acute myocardial infarction (AMI), and 40 with unstable angina pectoris (UAP), and 36 apparently healthy (control group) individuals. Patients with ACS were hospitalized at the Cardiology Clinic, Clinical Centre Sarajevo in the period OctoberDecember 2012. Laboratory analyses were conducted by standard methods. The accepted statistical significance level was p<0.05. Results: Serum levels of CRP and UA were higher in patients with ACS as compared to control group (p<0.01). The median serum UA was insignificantly lower, and CRP was significantly higher in patients with AMI compared to UAP (p=0.118 and p=0.001, respectively). Both CRP and UA correlated positively in both ACS and control groups (rho=0.246; p=0.028 and rho=0.374; p=0.027). A positive correlation between serum CRP and UA was noted in patients with AMI, but negative in patients with UAP (p>0.05). Conclusion: The correlation between CRP and UA in the patients with ACS indicates the association of oxidative stress and inflammation intensity in damaged cardiomyocytes. Correlation between UA and CRP in apparently healthy individuals indicates a possible role of UA as a marker of low-grade inflammation and its potential in risk assessment in cardiovascular diseases.
Keywords: angina; unstable; inflammation; myocardial infarction; oxidative stress